Seed fatty acid compositions of some Lathyrus taxa growing in Turkey - Emre, Irfan; Sahin, Ahmet; Yilmaz, Okkes; Genc, Hasan; Bahsi, Muammer (Soc Botanique France, 2011)
In the present study, fatty acid composition in mature seeds of the Lathyrus L. taxa were determined by using gas chromatography. Present results indicate that the seed oils of studied Lathyrus taxa have palmitic acid (C16:0) and stearic acid (C18:0) as major saturated fatty acids. Moreover, the present data show that oleic acid (C18:1), linoleic acid (C18:2 n 6) and a-linolenic acid (C18:3 n 3) are major unsaturated fatty acids in studied Lathyrus taxa. The highest oleic acid (C18:1 n 9) content is found in L. vinealis (26.8 %) but it is found at the lowest level in L. aphaca var. modestus (8.3 %). In addition, present study determines that investigated Lathyrus species have linoleic acid (42.8-62.8 %) and linolenic acid (9.2-12.9%) contents.
Keywords: gas chromatography; Lathyrus; saturated fatty acids; unsaturated fatty acids